Evaluation of the chemopreventive activity of grape skin extract using medium-term oral carcinogenesis assay induced by 4-nitroquinoline 1-oxide - De Moura, Carolina Foot Gomes; Soares, Glaucia Resende; Ribeiro, Flavia Andressa Pidone; Silva, Marcelo Jose Dias [UNESP]; Vilegas, Wagner [UNESP]; Santamarina, Aline Boveto; Pisani, Luciana Pellegrini; Estadella, Debora; Ribeiro, Daniel Araki (Anticancer Research USA, 2019)
Background/Aim: The aim of this study was to evaluate the chemoprotective potential of grape skin extract following rat tongue carcinogenesis induced by 4-nitroquinoline 1-oxide (4NQO). Materials and Methods: Male Wistar rats were distributed into four groups (n=5, per group): Control Group: free access to commercial diet and drinking water for 12 weeks; 4NQO Group: received 4NQO diluted in drinking water daily, for 12 weeks; Grape Skin Extract Group: free access to water and received grape skin extract incorporated with diet for 12 weeks; 4NQO + Grape Skin Extract Group: received 4NQO in drinking water daily and grape extract incorporated with diet for 12 weeks. Results: Animals treated with grape skin extract revealed a significant reduction in epithelial dysplasia. Also, 8-hydroxy-2' -deoxyguanosine (8-OHdG) and ki-67 immunoexpression was reduced in animals treated with grape skin extract. Western blot analysis showed a significant decrease of p-NFĸB p50 and MyD88 protein expression in the groups treated with grape skin extract. Copper-zinc superoxide dismutase, manganese superoxide dismutase, and catalase gene expression did not present any statistically significant differences (p>0.05). Conclusion: Grape skin extract displayed chemopreventive activity in oral carcinogenesis assays as depicted by its antioxidant, anti-proliferative and anti-inflammatory properties.
Keywords: 4-nitroquinoline 1-oxide; Antioxidant activity; Oral cancer; Proliferation; Rat; Toll like signaling pathway